A multivariate study of differentiating characters between three European species of the genus Lasiochernes Beier, 1932 (Pseudoscorpiones, Chernetidae) - Christophoryová, Jana; Krajčovičová, Katarína; Henderickx, Hans; Španiel, Stanislav (ZooKeys, 2016)
Morphological variation in three rarely collected European species of the genus Lasiochernes Beier, 1932 is thoroughly examined in the present study. Detailed descriptions of previously ignored morphological characters of Lasiochernes cretonatus Henderickx, 1998, Lasiochernes jonicus (Beier, 1929) and Lasiochernes pilosus (Ellingsen, 1910) are presented. The female of Lasiochernes cretonatus and the nymphs of Lasiochernes pilosus are described for the first time. Multivariate morphometric techniques (principal coordinate analysis and discriminant analyses) were employed to confirm morphological differentiation of the three Lasiochernes species and to identify the most reliable characters for their separation. The usefulness of particular body parts for species identification was evaluated. An identification key for the females of the Lasiochernes species studied is provided. Geographic distribution and habitat preferences of the three species are summarized.
Keywords: Caves; morphology; taxonomy; morphometric analysis; mole nests; pseudoscorpion